Automated Detection of coronaL MAss Ejecta origiNs for Space Weather AppliCations (ALMANAC) - Thomas Williams; Huw Morgan (Space Weather)
Abstract Alerts of potentially hazardous coronal mass ejection (CME) are based on the detection of rapid changes in remote observations of the solar atmosphere. This paper presents a method that detects and estimates the central coordinates of CME eruptions in Extreme Ultraviolet data, with the dual aim of providing an early alert, and giving an initial estimate of the CME direction of propagation to a CME geometrical model. In particular, we plan to link the Automated detection of coronaL MAss ejecta origiNs for space weather AppliCations (ALMANAC) method to the CME detection and characterization module of the Space Weather Empirical Ensemble Package, which is a fully automated modular software package for operational space weather capability currently being developed for the UK Meteorological Office. In this work, ALMANAC is applied to observations by the Atmospheric Imaging Assembly (AIA) aboard the Solar Dynamics Observatory (SDO). As well as presenting the method, a proof of concept test is made on a limited set of data associated with 20 halo CMEs recorded by the Coordinated Data Analysis Workshop (CDAW) catalog near the activity maximum of solar cycle 24. SDO/AIA data for each event is processed at 6 min cadence to identify the on‐disk location and time of each CME. The absolute mean deviance between the ALMANAC and CDAW source event coordinates are within 37.05 ± 29.71 min and 11.01 ± 10.39°. These promising results give a solid foundation for future work, and will provide initial constraints to an automated CME alert and forecasting system.